Durability of and role of AKT in FGF7p urothelial protection against cyclophosphamide - Sridhar Tatarao Narla; Lori Rice; David Ostrov; Daniel Scott Bushnell; Joanne Lindsey Duara; Carlton Matthew Bates (Physiological Reports, 2022)
Abstract We previously identified a peptide derived from human fibroblast growth factor 7 (FGF7p) that blocks urothelial apoptosis similar to full‐length FGF7, although effects of FGF7p on urothelial repair are unknown. Also, while urothelial AKT activation downstream of FGF7p correlated with the anti‐apoptotic effects, we have not directly interrogated the role of AKT in mediating the cytoprotection. Our goal was to assess effects of FGF7p on urothelial repair and the role of AKT signaling in mediating the cytoprotective effects of FGF7p. We performed hematoxylin and eosin (H&E), TUNEL, and/or immunofluorescence (IF) staining for various markers in FGF7p‐treated mice 28 days after giving cyclophosphamide or after co‐administering a systemic AKT antagonist with FGF7p 24 h after cyclophosphamide. Vehicle‐treated and injured mice had hyperplastic urothelium, incomplete return of mature superficial cell markers, ongoing proliferation, and continued presence of basal progenitor markers 28 days after injury; conversely, FGF7p‐treated mice had normal numbers of urothelial cell layers, nearly complete return of superficial cell markers, limited proliferation and fewer basal progenitor cells 28 days post‐injury. Vehicle‐treated mice also had ectopic lumenal basal progenitor cell markers, while FGF7p had none 28 days after cyclophosphamide. Co‐administration of an AKT inhibitor largely abrogated FGF7p‐driven AKT activation and cytoprotection in urothelium 24 h after injury. Thus, FGF7p drives faster and higher fidelity urothelial repair by limiting apoptotic injury via AKT signaling, similar to full‐length FGF7. Finally, FGF7p is much less expensive to synthesize and has a longer shelf life and higher purity than FGF7.